2002
DOI: 10.1046/j.1365-2591.2002.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of the prevalence and technical quality of root canal treatment in a French subpopulation

Abstract: The results demonstrate a high prevalence of root-filled teeth and poor technical quality of treatment. Roots presenting with acceptable root fillings were associated with a lower prevalence of periapical pathology (P < 0.001). Posts in roots were associated with periapical pathology significantly more than in roots without posts (P < 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
194
12
21

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(256 citation statements)
references
References 37 publications
29
194
12
21
Order By: Relevance
“…6 Cross sectional studies have reported 20%-60% of treatment failure and 52% of endodontic failure in Iranian population. [7][8][9][10] Existence of intracanal microorganisms would lessen the treatment outcomes of endodontic re-treatment comparing to primary endodontic treatment. 2 Based on the previous studies, bacterial microflora in teeth with failed endodontic treatment is different from the microflora of the primary endodontic infection.…”
Section: Introductionmentioning
confidence: 99%
“…6 Cross sectional studies have reported 20%-60% of treatment failure and 52% of endodontic failure in Iranian population. [7][8][9][10] Existence of intracanal microorganisms would lessen the treatment outcomes of endodontic re-treatment comparing to primary endodontic treatment. 2 Based on the previous studies, bacterial microflora in teeth with failed endodontic treatment is different from the microflora of the primary endodontic infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of the quality of RF, various criteria were used in the selected studies: three studies used the distance of the endodontic filling from the root apex, 16,21,23 three studies used the filling density and its distance from the apex, 17,18,25 three studies defined the parameter as being the presence of filling material in the root canal 1,9,19 four studies preferred criteria proposed by other authors 20,22,26,27 and in one article the authors created their own guidelines 24 ( Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…However, some studies have reported an increased prevalence of apical periodontitis in teeth restored with clamps [9]. In a study carried out by Tavares et al [19], out of 458 teeth with dental post, 315 (65%) teeth were involved with chronic apical periodontitis.…”
Section: Discussionmentioning
confidence: 97%
“…The data obtained from Scandinavian and other European countries has shown a high prevalence of apical periodontitis due to the poor quality of root canal treatment [5][6][7][8][9][10][11]. On the other hand, apical periodontitis usually occurs as a chronic disease and has few or no clinical symptoms [5,12].…”
mentioning
confidence: 99%